The role of the MICE sector in Singapore's tourism policy. A historical perspective - Mena Navarro, Alfredo; Almeida-García, Fernando; Cortés-Macías, Rafael (Taylor & Francis, 2022)
The present study develops a holistic analysis framework to unravel the complexity of the tourism policy process, with a special focus on the Meetings, Incentives, Conferences and Exhibitions (MICE) sector in Singapore. A qualitative approach combining two research methods was adopted: qualitative content analysis and documentary analysis. This is a relatively novel perspective in tourism studies. The vision of the tourism policy process offered by the research, through the integration of multiple levels of analysis (micro and macro) and its historical contextualisation, led to a better understanding of the evolution of Singapore as a MICE destination. The paper identifies a series of patterns of action over the last 50 years in the unique and successful MICE tourism development model of this city–state. These have included interventionism, public-private collaboration, long-term planning, and innovation. By using the Singaporean MICE sector as a case study, the paper also provides valuable insights into the dynamics of the tourism policy process. The findings indicate that public policy aimed at the development of a specific tourism segment, namely MICE, should not be analysed in isolation from other policy areas. It is an activity that is embedded within broader economic, political and cultural processes.
https://openpolicyfinder.jisc.ac.uk/id/publication/5709
Keywords: Política turística - Singapur; Turismo de negocios; Singapore; MICE; Tourism policy; Tourism success; Qualitative research